2022
DOI: 10.32604/phyton.2022.020629
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa L.) Breeding among Hassawi Landrace and Egyptian Genotypes for Stem Borer (Chilo agamemnon Bles.) Resistance and Related Quantitative Traits

Abstract: Rice stem borer (Chilo agamemnon Bles.) is a primary insect pest of rice and is a major limiting factor to rice production. Breeding for insect-resistant crop varieties has been an economic way of integrated pest management (IPM) as it offers a viable and ecologically acceptable approach. This study was aimed to evaluate rice genotypes for their resistance against rice stem borer. Seven parental genotypes with twenty one F 1 crosses were evaluated for genotypic variation in field experiments. Analysis of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In addition, the mean squares due to lines vs. testers were significant for all traits, which indicated that female and male parents differed significantly for these traits. These results are similar to those obtained by [34,35].…”
Section: Anova Analysissupporting
confidence: 91%
“…In addition, the mean squares due to lines vs. testers were significant for all traits, which indicated that female and male parents differed significantly for these traits. These results are similar to those obtained by [34,35].…”
Section: Anova Analysissupporting
confidence: 91%
“…The estimates of GCA effects among the genotypes for short-stature traits showed that the three rice parental genotypes, i.e., Sakha 108, Sakha102, and Giza 179, were indicative as the best general combiners for short stature and grain yield plant -1 except Sakha102, which has the negative GCA effects in grain yield plant -1 ( Srujana et al, 2017;Sandeep et al, 2018;Fahmi et al, 2018;Al-Daej et al, 2022). As for SCA four crosses, namely, Sakha105 × Giza179, Sakha105 × Sakha108, Sakha106 × Giza179, and Sakha108 × Sakha109, these showed significant positive SCA effects for all the traits.…”
Section: Developingmentioning
confidence: 99%
“…This will need to study the genetic diversity and genetic background for each variety, which will be useful to improve the agronomic traits ( Sabri et al, 2020 , Zhong et al, 2021 ). Studies on genetic diversity are crucial for breeding and improvement projects because they guarantee the appropriate use of germplasm resources and a productive breeding system for the promotion of closely related crop species ( Al-Daej et al, 2022 ). Until recently, morphological characterization had proven effective in identifying genetic material.…”
Section: Introductionmentioning
confidence: 99%